2014
DOI: 10.1007/s00192-014-2390-1
|View full text |Cite
|
Sign up to set email alerts
|

Faecal incontinence 20 years after one birth: a comparison between vaginal delivery and caesarean section

Abstract: Late FI and AI prevalences were higher after VD compared with CS. Perineal tear (≥second degree) versus no tear doubled the prevalence of FI. FI prevalence was similar after a CS and a VD combined with episiotomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
26
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 28 publications
3
26
3
Order By: Relevance
“…A registry-based national cohort study of primiparous women giving birth between 1985 and 1988 and having no further births reported that prevalent fecal incontinence 20 years later was more common after vaginal delivery than cesarean section (14.5 versus 10.6%, OR 1.43, 95% CI 1.16-1.77) [19]. The long-term effects of mode of delivery and anal sphincter trauma have been investigated in several recent studies.…”
Section: Risk Factors For Accidental Bowel Leakage (Fecal Incontinence)mentioning
confidence: 99%
“…A registry-based national cohort study of primiparous women giving birth between 1985 and 1988 and having no further births reported that prevalent fecal incontinence 20 years later was more common after vaginal delivery than cesarean section (14.5 versus 10.6%, OR 1.43, 95% CI 1.16-1.77) [19]. The long-term effects of mode of delivery and anal sphincter trauma have been investigated in several recent studies.…”
Section: Risk Factors For Accidental Bowel Leakage (Fecal Incontinence)mentioning
confidence: 99%
“…The prevalence of PFD varies widely according to the population studied and the definition used and is reported to be 3–12% for symptomatic pelvic organ prolapse, 15–35% for urinary incontinence and 3–14% for fecal incontinence . Overlapping of symptoms of two or three conditions is common .…”
Section: Introductionmentioning
confidence: 99%
“…However, urinary symptoms start during pregnancy due to an increase in urine production, increased cardiac output, and the weight of the pregnant uterus pressing on the bladder. The key risk factor associated with the development of UI is childbirth and in particular, the trauma associated with the first vaginal birth, however, there are other epidemiological factors during pregnancy that predict the development of UI such as parity, hereditary factors, ethnicity, and obesity …”
Section: Methodsmentioning
confidence: 99%